Cracking the Toll-like receptor code in fungal infections - Cunha, Cristina (2010)
Innate control of fungal infection requires the specific recognition of invariant fungal molecular structures by a variety of innate immune receptors, including Toll-like receptors. In addition to the role in inducing protective immune responses, Toll-like receptor engagement may paradoxically favor fungal infections, by inducing inflammatory pathology and impairing antifungal immunity. Although the dissection of complex genetic traits modulating susceptibility to fungal infections is complex, the contribution of host genetics may hold the key to elucidating new risk factors for these severe, often fatal diseases. Understanding host-pathogen interactions at the innate immune interface will eventually lead to the development of new therapeutics and genetic markers in fungal infections.